Rapid penetration into granular media : visualizing the fundamental physics of rapid earth penetration - Iskander, Magued; Bless, Stephan; Omidvar, Mehdi (Elsevier Ltd., 2015)
Rapid Penetration into Granular Media: Visualizing the Fundamental Physics of Rapid Earth Penetration introduces readers to the variety of methods and techniques used to visualize, observe, and model the rapid penetration of natural and man-made projectiles into earth materials. It provides seasoned practitioners with a standard reference that showcases the topic's most recent developments in research and application. The text compiles the findings of new research developments on the subject, outlines the fundamental physics of rapid penetration into granular media, and assembles a comprehensive collection of experimental and numerical methods to study the problem.